2014
DOI: 10.1128/jb.01907-14
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PG2212 Zinc Finger Protein in the Regulation of Oxidative Stress Resistance in Porphyromonas gingivalis W83

Abstract: dThe adaptation of Porphyromonas gingivalis to H 2 O 2 -induced stress while inducible is modulated by an unknown OxyR-independent mechanism. Previously, we reported that the PG_2212 gene was highly upregulated in P. gingivalis under conditions of prolonged oxidative stress. Because this gene may have regulatory properties, its function in response to H 2 O 2 was further characterized. PG2212, annotated as a hypothetical protein of unknown function, is a 10.3-kDa protein with a cysteine 2-histidine 2 (Cys 2 Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…McKenzie et al indicated that the inactivation of pg1372 (encoding a protein with DNA-binding properties) virtually eliminated the ability of P. gingivalis to adapt to oxidative stress [ 9 ]. Dou et al showed that a PG2212 (encoding a zinc finger protein) isogenic mutant strain of P. gingivalis exhibited an increased sensitivity to H 2 O 2 [ 10 ]. In this study, we cultured P. gingivalis W83 and its sialidase-deficient mutant strain under stressful environmental conditions, including various pH values, temperatures and oxidative stress conditions, and compared the growth, morphology, tolerance, virulence factors and biofilm formation of these two strains to investigate the roles of sialidase in the adaptation of P. gingivalis to these stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…McKenzie et al indicated that the inactivation of pg1372 (encoding a protein with DNA-binding properties) virtually eliminated the ability of P. gingivalis to adapt to oxidative stress [ 9 ]. Dou et al showed that a PG2212 (encoding a zinc finger protein) isogenic mutant strain of P. gingivalis exhibited an increased sensitivity to H 2 O 2 [ 10 ]. In this study, we cultured P. gingivalis W83 and its sialidase-deficient mutant strain under stressful environmental conditions, including various pH values, temperatures and oxidative stress conditions, and compared the growth, morphology, tolerance, virulence factors and biofilm formation of these two strains to investigate the roles of sialidase in the adaptation of P. gingivalis to these stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…DNA microarray gene expression analyses were performed using the Roche NimbleGen customer arrays (100910_CW_P_ging_w83_expr_HX12) according to the standard NimbleGen procedure (NimbleGen Arrays User's Guide: Gene Expression Analysis v5.1) as previously reported previously (Dou et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Purified, recombined plasmid was used to transform △PG0352 via electroporation. Transformants were selected using TSB agar plates with 5 μg/mL clindamycin and 1 μg/mL tetracycline 25 …”
Section: Methodsmentioning
confidence: 99%
“…Transformants were selected using TSB agar plates with 5 mg/mL clindamycin and 1 mg/mL tetracycline. 25 Epi4 Cell Culture Epi4, an SV40 T-antigen-immortalized GEC line, 26 was maintained in medium ¶ supplemented with antibiotics (100 units/mL penicillin, 100 mg/mL streptomycin # ) at 37°C with 5% CO 2 .…”
Section: Construction Of Pg0352 Mutant and Complemented Strainsmentioning
confidence: 99%